Beyond Economic Interests: Attitudes toward Foreign Workers in Australia, the United States and East Asian Countries. (September 2014) - Tsai, Ming-Chang; Tzeng, Rueyling
We compare attitudes toward foreign workers between two wealthy Western and four developing East Asian countries, using data from the 2006 and 2008 Asian Barometer surveys to test hypotheses on economic interests, cultural supremacy, and global exposure. Respondent majorities in all six countries expressed high levels of restrictivism. Regression model results indicate a consistent cultural superiority influence across the six countries, but only minor effects from economic interest factors. Mixed outcomes were noted for the global exposure variables.